Linux shell scripting cookbook : over 110 incredibly effective recipes to solve real-world problems, automate tedious tasks, and take advantage of Linux's newest features - Flynt, Clif; Tushar, Shantanu; Lakshman, Sarath (Packt Publishing, 2017)
Do amazing things with the shell About This Book Become an expert in creating powerful shell scripts and explore the full possibilities of the shell Automate any administrative task you could imagine, with shell scripts Packed with easy-to-follow recipes on new features on Linux, particularly, Debian-based, to help you accomplish even the most complex tasks with ease Who This Book Is For If you are a beginner or an intermediate Linux user who wants to master the skill of quickly writing scripts and automate tasks without reading the entire man pages, then this book is for you. You can start writing scripts and one-liners by simply looking at the relevant recipe and its descriptions without any working knowledge of shell scripting or Linux. Intermediate / advanced users, system administrators / developers, and programmers can use this book as a reference when they face problems while coding. What You Will Learn Interact with websites via scripts Write shell scripts to mine and process data from the Web Automate system backups and other repetitive tasks with crontab Create, compress, and encrypt archives of your critical data. Configure and monitor Ethernet and wireless networks Monitor and log network and system activity Tune your system for optimal performance Improve your system's security Identify resource hogs and network bottlenecks Extract audio from video files Create web photo albums Use git or fossil to manage revision control and interact with FOSS projects Create and maintain Linux containers and Virtual Machines Run a private Cloud server In Detail The shell is the most powerful tool your computer provides. Despite having it at their fingertips, many users are unaware of how much the shell can accomplish. Using the shell, you can generate databases and web pages from sets of files, automate monotonous admin tasks such as system backups, monitor your system's health and activity, identify network bottlenecks and system resource hogs, and more. This book will show you how to do all this and much more. This book, now in its third edition, describes the exciting new features in the newest Linux distributions to help you accomplish more than you imagine. It shows how to use simple commands to automate complex tasks, automate web interactions, download videos, set up containers and cloud servers, and even get free SSL certificates. Starting with the basics of the shell, you will learn simple commands and how to apply them to real-world is...